FORMULASI PENDIDIKAN PESANTREN NGALAH DALAM MEMBENTUK KARAKTER RELIGIUS PLURALISTIK - Dina Uswatun Khasanah; Achmad Yusuf; Asrul Anan (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2022)
Pondok Pesantren Ngalah is a boarding school that has close relationships with non-Muslims. Often Pondok Pesantren Ngalah holds events that invite non Muslim brothers, and vice versa. Often non-Muslim brothers also visit Pondok Pesantren Ngalah to hold events such as Live in Pendeta. Based on these problems, this study aims to know how the formulation of Pondok Pesantren Ngalah education in shaping pluralistic religious character. The type of research used in this study is qualitative research type with case study approach in Pondok Pesantren Ngalah. The results of this study showed that the formulation of Ngalah pesantren education in forming pluralistic religious character is diferent as that delivered by Glock and Stark which includes five dimensions namely The experiental dimension or informal education and activities with non Muslims, The ritualistic dimension or religious activities in Pondok Pesantren Ngalah, The intellectual dimension or formal education level , informal, and non-formal, The consequential dimension or pesantren culture, and The ideological dimension. In addition, the process of applying pesantren education through religious activities, learning the yellow book, pesantren culture, and active role in pluralistic activities.